Gambaran Self confidence pada Mahasiswi di Jember yang Menggunakan Natural Makeup - Tristiana, Avia; Ervina, Iin; Handayani, Panca Kursistin (Jurnal Psikologi, 2024)
Self confidence is a person's positive attitude and behavior so that they can express themselves more freely, not feeling anxious, afraid and not confident in their abilities. One factor that can influence Self confidence is physical appearance. This is a motivation for women to improve their appearance by using makeup to look attractive. This research aims to understand the self-confidence of female students in Jember who use natural make-up. The method in this research is descriptive quantitative. The population in the research was female university students in Jember. the number of respondents was 120 people. The sampling technique uses non probability sampling with accidental sampling. The data collection technique uses a confidence scale in using natural makeup and is measured using a Likert scale. The analysis methods used include validity tests, reliability tests, normality tests and descriptive tests. The research results show that out of 120 female students at universities in Jember, 59 female students with a percentage of 49% tend to have high self-confidence, and 61 female students with a percentage of 51% tend to have low self-confidence. The level of self-confidence based on aspects shows that the aspect of self-love is 53% and positive thinking is 66% in the high category, while the low aspects are self-understanding at 47% and clear life goals at 37%. So students need to develop self-confidence in using natural make-up through various aspects that they feel are lacking, such as self-understanding and clear life goals.